Real-time Cloud Applications - Salamah, Muhammed; Guler, Nivine (CRC Press, 2024)
The revolution of Internet of Things (IoT) technologies, especially the advances in mobile communications brought by 5G and 6G standards, allows innovative application domains to enter the cloud world gradually such as real-time applications. Real-time applications that require data to be captured and processed under stringent time constraints are becoming more popular. With the use of the Internet to access these applications, cloud computing has become a main tool for the realization of utility model of computing. The main strengths of cloud computing include standardized platforms and management support services, massive scalability, global access, flexible infrastructure, incremental usage controls, and pricing. Cloud computing has become a viable technological means to provide a scalable, demand-driven, and ubiquitous computing infrastructure for many applications. It is the driving force for the major evolutionary technical developments in the information technology world and the IT marketplace. Along with ultra-reliable and low-latency communication infrastructures, computing and machine learning (ML) algorithms are the most important enablers of cloud various domains such as the navy, where efficient alarm systems for critical situations and remote monitoring should be supported in real time. Besides the navy domain, unmanned vehicle is another type of real-time application that runs on the cloud. © 2024 CRC Press.